Analysis of The Implementation of The Merdeka Learning Curriculum at Buntu Ampang Primary School - Putri Putri; Erwin Nurdiansyah; Supriadi Supriadi (Program Studi Pendidikan Sekolah Dasar Fakultas Keguruan dan Ilmu Pendidikan Universitas Islam Makassar, 2026)
This study aims to analyze the implementation of the Merdeka Belajar curriculum at SDN Buntu Ampang, Baroko District, Enrekang Regency, through the implementation process, obstacles encountered, and the impacts after its implementation. This study uses a qualitative approach with a descriptive research type. The research subjects consisted of the principal, teachers, and students. Data collection techniques were carried out through interviews, observation, and documentation. Data analysis was carried out through the stages of data reduction, data presentation, and drawing conclusions. The results of the study indicate that the implementation of the Merdeka curriculum at SDN Buntu Ampang has been carried out quite well, especially in the planning and implementation of learning that is more flexible and student-centered. Teachers act as facilitators by using teaching modules and various learning methods, such as discussions, group work, and project-based learning. However, in the implementation there are still several obstacles, including limited internet access, and minimal training and mentoring of teachers related to the Merdeka curriculum. The impact of the implementation of the Merdeka curriculum shows an increase in learning motivation, activeness, creativity and independence of students in the learning process. Therefore, the implementation of the Merdeka curriculum needs to be supported by improved facilities and infrastructure as well as ongoing training for teachers to ensure optimal implementation.